Documenting moths (Lepidoptera, Heterocera) in Bengaluru urban district, Karnataka, India - Ravishankar, Lochana; Gowda , Yashwanth Nagathihalli Mohan Kumar; Munirathinam, Jayashankar (ENTOMON, 2026)
During the observation in three areas of Bengaluru Urban District, moths belonging to 42 genera, of which 39 were identified until the species level, belonging to seven families. Thirteen species of moths were identified from 18 samples in the study area I, and 17 species in II and 12 in study area III. This checklist would serve as a first milestone for further surveys on the diversity of moths of the Bengaluru region.